Analysis of the Application of WFH Policies in Overcoming Pollution Problems in Jakarta - Ferdinand Salomo Leuwol*; Maryam Salampessy; Wuri Astamala Dewi; Budi Sulistiyo Nugroho; Ramadhany Nugroho (Universitas Syiah Kuala, 2023)
One of the problems that worries Jarta is that the pollution problem in Jakarta is getting worse. To overcome this problem, the Provincial Government of DKI Jakarta launched a WFH policy for civil servants which will be implemented at the end of September 2023. This study aims to analyze the implementation of this policy whether it is effective in overcoming pollution problems or not. This research is a qualitative research with a descriptive approach. The data used in this study is secondary data obtained from scientific journals, books, written magazines, newspapers, and so on. The analysis technique in this study uses sequence analysis techniques which include library observation, data collection, data processing, data reduction and selection, and drawing conclusions. The results of the study show that the implementation of the WFH policy is effective when it is accompanied by a comprehensive concept regarding supervision, sanctions for violations, and accompanied by other policies that can address the pollution problem in Jakarta.